2009
DOI: 10.1007/s10661-009-1181-5
|View full text |Cite
|
Sign up to set email alerts
|

Total metal levels in crayfish Astacus leptodactylus (Eschscholtz, 1823), and surface sediments in Lake Terkos, Turkey

Abstract: The aim of this study was to determine the total metal accumulation (aluminium, copper, manganese, lead, cadmium and iron) in different organs and eggs of Astacus leptodactylus (Eschscholtz, 1823) and sediments total metal contents (aluminium, copper, manganese, lead, cadmium, iron, zinc, chromium, nickel) in Lake Terkos. Water and sediment samples were collected from two stations at two different depths (1 and 2 m) of Lake Terkos in May 2008. Crayfish samples were collected by trammel net at the same region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 29 publications
6
11
0
Order By: Relevance
“…Similar associations are present between Mn and both Cd and Pb in female muscle tissue. Kurun et al reported the Mn-Al correlation coefficient to be ?0.79 in a study performed on Astacus leptodactylus (Terkos Lake) (Kurun et al 2010). In the present study, correlation coefficients of Mn-Al in muscle tissue were found to be similar (?0.745 for male and ?0.675 for female specimens), whereas no correlation was observed in hepatopancreas tissue for both sexes; a weak positive Mn-Al correlation was present in The component group (group 1 or group 2, respectively) to which the variable in question belongs exoskeleton and gill for male specimens, but no such correlation was detected in those tissues for the female cohort.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Similar associations are present between Mn and both Cd and Pb in female muscle tissue. Kurun et al reported the Mn-Al correlation coefficient to be ?0.79 in a study performed on Astacus leptodactylus (Terkos Lake) (Kurun et al 2010). In the present study, correlation coefficients of Mn-Al in muscle tissue were found to be similar (?0.745 for male and ?0.675 for female specimens), whereas no correlation was observed in hepatopancreas tissue for both sexes; a weak positive Mn-Al correlation was present in The component group (group 1 or group 2, respectively) to which the variable in question belongs exoskeleton and gill for male specimens, but no such correlation was detected in those tissues for the female cohort.…”
Section: Resultssupporting
confidence: 70%
“…Although previous studies have reported the trends of metal accumulation on this species, accumulation effects of each metal on the accumulation trends of other metals has still not been elucidated on this species and even in crayfish in general (Guner 2007;Naghshbandi et al 2007;Kurun et al 2010). The purpose of this study therefore was to understand the accumulation and correlation trends of several metals and a metalloid, with emphasis placed on the relative accumulation rates of metal isotopes.…”
mentioning
confidence: 96%
“…It could explain the reduced amount of Mn in the exoskeleton of females in comparison with males. Kurun et al (2010), Protasowicki et al (2013) and Tunca et al (2013b) confirmed lower amounts of Mn in the muscle of females than males. Our analyses of spiny-cheek crayfish indicated a higher concentration of Hg was detected in the muscle (Table 4) but gender dependent differences were only observed for exoskeleton tissues (Table 5).…”
Section: Resultsmentioning
confidence: 92%
“…[14,15] As such, different tissues may be found to accumulate higher concentrations of the same metal in different studies. [16,17] Sex is another factor altering the accumulation trends of metals and may be particularly important during the reproductive season. Female crayfish of different species were found to accumulate less As, Ni and Cd in their gills when tested during the reproductive season, [16,18] which may suggest that these metals are sequestered within the eggs.…”
Section: Discussionmentioning
confidence: 99%